A Model for Evaluating the Crystallinity Quality of Single Crystals Grown by the Floating Zone Technique. Issue 1 (20th November 2022) - Xu, Benyan; Li, Zhenyou; Wang, Kunpeng; Wang, Xuejiao; Zhang, Jianxiu; Liang, Lanju; Li, Longfei; Ren, Yanbiao; Liu, Yong; Liu, Meng; Xue, Dongfeng
Abstract: The floating zone technique is a popular method for crystal growth of nonconventional superconductors and magnetic materials. However, the quality must be characterized with particular care with respect to their actual crystallinity since not everything grown by floating zone method is a single crystal. In this paper, the molten‐zone sensitive material LiCoPO4 has been grown by the floating zone method using Co(NO3 )2 ∙6H2 O and CoO precursors, respectively, abbreviated as LCPN and LCPO . The grown materials are characterized regarding their chemical composition, phase purity, crystal perfection, and orientation. In order to optimize crystal growth and quantitatively characterize its crystallinity quality, the development factor ( V ) has been proposed to determine the growth rate of the grains, while the orientation deviation factor ( δ ) for assessing the quality of the grown crystals. The development factors V for LCPN and LCPO are calculated to be 0.05 and 0.09, respectively, indicating that the grains of LCPO develop faster than those of LCPN . At the same time, the orientation deviation factor of LCPO exceeds that of LCPN ( δ (LCPO ) = 2.00, δ (LCPN ) = 0.77) suggesting a higher quality for the latter. This model provides significant guidance for the evaluation of other materials grown by the floating zone method. Abstract : LiCoPO4 single crystals have been grown by the floating zone method using Co(NO3 )2 ∙6H2 O and CoO precursors. An evaluation method that provides quantitative information of crystal quality and the growing capability of grains is developed. Two indexes are proposed to help making a fair comparison of the obtained crystals and their properties.